Tax Law Design and Drafting, Volume 1 - Thuronyi, Victor (International Monetary Fund, 1996)
Edited by Victor Thuronyi, this book offers an introduction to a broad range of issues in comparative tax law and is based on comparative discussion of the tax laws of developed countries. It presents practical models and guidelines for drafting tax legislation that can be used by officials of developing and transition countries. Volume I covers general issues, some special topics, and major taxes other than income tax.